Avifaunal Diversity of Barandabhar Corridor Forest, Chitwan, Nepal - Jha, Praveen Kumar; Dhakal, Debendra Prasad (International Research Journal of MMC, 2021)
The main aim of the study was to analyze the avifaunal diversity of Chitwan, Nepal. The avifaunal diversity at six transects of Barandabhar Corridor Forest in Chitwan district was carried out during two visits (autumn and spring) in 2020-2021. The line transect method was used to cover most of the study area. In total, 125 species of birds representing 18 orders and 59 families were recorded. The highest number of bird species i.e. (56) 44.8% were represented by order Passeriformes along with 34 families. The highest number of species was found in family Picidae (9) 7.2% followed by Cuculidae (8) 6.4% and least number (1) 0.8% in other 31 families. The seasonal status of species was Autumn (84) and Spring (116). The relative abundance of species was Very Common (60), Common (40), Uncommon (16), and Rare (9). According to the National Red List of Nepal’s Birds, 110 species were in the Least Concern category, eight species were in the Near Threatened category, six species were in the Vulnerable category and one species was in the Critically Endangered category. It was noted that major threats to the birds were illegal fishing, noise pollution, firewood collection, illegal cattle grazing, and invasive alien plant species. One Globally Threatened Bird Lesser Adjutant Leptoptilos javanicus was also noted.